Bio-based volatile fatty acid production and recovery from waste streams: Current status and future challenges. (November 2018) - Atasoy, Merve; Owusu-Agyeman, Isaac; Plaza, Elzbieta; Cetecioglu, Zeynep
Graphical abstract: Highlights: Bio-based VFA production is getting attention due to wide range usage area. VFA production and recovery were reviewed in different aspects. Enhanced VFA production and efficient recovery from waste are main challenges. Bio-augmentation and in-line VFA recovery are seen as promising approaches. Abstract: Bio-based volatile fatty acid (VFA) production from waste-stream is getting attention due to increasing market demand and wide range usage area as well as its cost-effective and environmentally friendly approach. The aim of this paper is to give a comprehensive review of bio-based VFA production and recovery methods and to give an opinion on future research outlook. Effects of operation conditions including pH, temperature, retention time, type of substrate and mixed microbial cultures on VFA production and composition were reviewed. The recovery methods in terms of gas stripping with absorption, adsorption, solvent extraction, electrodialysis, reverse osmosis, nanofiltration, and membrane contractor of VFA were evaluated. Furthermore, strategies to enhance bio-based VFA production and recovery from waste streams, specifically, in-line VFA recovery and bioaugmentation, which are currently not used in common practice, are seen as some of the approaches to enhance bio-based VFA production.